Colorimetric detection of residual quaternary ammonium compounds on dry surfaces and prediction of antimicrobial activity using bromophenol blue. (5th December 2020) - Burel, C.; Direur, G.; Rivas, C.; Purevdorj‐Gage, L.
Abstract: Controlling and monitoring the residual activity of quaternary ammonium compounds (QACs) are critical for maintaining safe yet effective levels of these agents in the environment. This study investigates the utility of bromophenol blue (BPB) as a safe, rapid and user‐friendly indicator to detect in situ residual QACs dried on hard, non‐porous surfaces, as well a means to assess their antimicrobial efficacy. At pH 7, BPB has a purple colour which turns blue upon its complexation with QACs such as didecyldimethylammonium chloride (DDAC). BPB itself has no antimicrobial properties up to 400 ppm. Within the range of 0–400 ppm, BPB colour change was tied to specific DDAC antimicrobial performances with a detection threshold of 100 ppm. BPB concentration and application volume could be adjusted such that a colour shift from purple to blue correlated with a set percent reduction (>99·9%) in test bacteria ( Staphylococcus aureus and Klebsiella aerogenes ). The BPB solutions developed in this study yielded similar colour shifts on polycarbonate and stainless steel surfaces and did not cross‐react with chemical ingredients commonly found in sanitizers and disinfectant products. Overall, this study suggests that BPB provides a simple solution to safely monitor the post‐application level and biocidal activity of residual dried QACs on surfaces. Abstract : Significance and Impact of the Study: Excessive use of antimicrobial quaternary ammonium compounds (QACs) can have adverse effects on health and ecosystems. Compatible with chemicals commonly used in sanitizers, non‐toxic bromophenol blue (BPB) was used to detect residual amounts of QACs such as didecyldimethylammonium chloride (DDAC) on hard non‐porous surfaces. Once deposited, BPB solutions turn from purple to blue upon complexation with DDAC in a quantitative, stoichiometric fashion. The colour shift is linked to a 99·9% reduction in bacteria for both Staphylococcus aureus and Klebsiella aerogenes . Thus, BPB provides a simple solution to safely monitor the post‐application level and biocidal activity of dried QACs on surfaces.